Perbedaan Tingkat Kepuasan Pasien Bpjs Dengan Pasien Umum di RSUD Dr. Soediran Mangun Sumarso Wonogiri - Sari, Primatika Ambar; , dr. Burhanudin Ichsan, M.Med,Ed.,M.Kes; , dr. Yusuf Alam Romadhon, M.Kes (2015)
Background. Satisfaction of patient is considered an important dimension and one of main indicators of health facility resulting from effect of health service of a hospital and it makes measurement of patient satisfaction to be important component. Purpose of the Research. Purpose of the research is to analyze difference of satisfaction levels between patient with national health program and regular patient in Dr. Soediran Mangun Sumarso General Hospital, Wonogiri. Method. The research is observational one with cross-sectional approach. Sample of the research was 37 national health program patients and 37 regular patients taken by using purposive sampling. The data was analyzed statistically by using unpaired t-test. Results. The research found that satisfaction level of regular patients was 106.14 in average and those of national health program patients was 66.62. So that, it can be concluded that mean score of satisfaction level of regular patients was higher than national health program patients. The p-value (sig) of 0.001 met normal criteria, namely p<0.05, so that the research found significant difference. Conclusion. Based on results of the research, it can be concluded that a significant difference of satisfaction levels between national health program patients and regular patients was found in Dr. Soediran Mangun Sumarso General Hospital, Wonogiri with regular patients had higher level of satisfaction than national health program patients with mean difference was 39.51%.